2017
DOI: 10.22214/ijraset.2017.4109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Beam-Column Joint in a Pre-stressed Concrete Structure using Finite Element Method

Abstract: Pre-stressed concrete is the type of concrete in which internal stresses of a suitable magnitude and distribution are induced so that the stresses resulting from external loads are counteracted to a desired degree. Pre-stressed concrete structures exhibit high strength and durability. These types of structures are very popular in use in bridge deck systems and culverts. However, various elements of pre-stressed concrete member undergo different types of stresses. The weakest element of these being beam column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results stated that the changes in the forces due to the presence of rigid diaphragm is effective and results concluded that due to introduction of pretension Ing slab, structure become more stable and stiffer in comparison. It can be said that P-delta analysis results in observing overturning moment and rotational forces using analysis tool Ansys [4].…”
Section: P-delta Analysismentioning
confidence: 99%
“…The results stated that the changes in the forces due to the presence of rigid diaphragm is effective and results concluded that due to introduction of pretension Ing slab, structure become more stable and stiffer in comparison. It can be said that P-delta analysis results in observing overturning moment and rotational forces using analysis tool Ansys [4].…”
Section: P-delta Analysismentioning
confidence: 99%